Response of garlic clones to the combined effect of planting densities and nitrogen supply modes - Aguado, German Dario; Portela, Jose Antonio; Lipinski, Victor Mario (Asociación Argentina de Horticultura (ASAHO), 2024)
Inefficient fertilization practices, as well as relatively low planting densities in garlic crops, determine high production costs and yields below crop potential. In order to study the response of Mediterranean garlic clones to combinations of planting densities and nitrogen supply modes, three clonal cultivars ("Unión", late white garlic, "Gostoso INTA" and "Rubí INTA", red garlic) were tested at the Agricultural Experimental Station La Consulta INTA (33.7 S, 69.7 W, 940 m.a.s.l.). Six arrangements combining two planting densities (28 and 56 plants.m-2 ) and three nitrogen supplying modes (without fertilizing; 180 kg.ha-1 until bulbing beginning; 70% of the dose until bulbing beginning and 30% from rapid bulb growth), were established. With 33 physiological and environmental covariates, principal components analysis and partial-least squares regression analysis were performed. Doubling the traditional plant population substantially increased total yield of garlic, with better response in the late white clone. The stage of rapid vegetative growth was defined as of main importance in determining the response to high density in Mediterranean clones. Nitrogen dose partitioning did not show consistent differential responses. Those findings provide new insights for improving crop-ecophysiology-based management practices in garlic, in terms of plant density and cultivar selection.